One new species of Phryganogryllacris (Orthoptera: Ensifera: Gryllacrididae) from Yunnan, China - Chen, Xiaoqin; Yang, Ziyi (Zootaxa, 2024)
Phryganogryllacris is a large Raspy Cricket genus comprising 26 known valid species widely distributed in temperate and tropical Asia. In this paper, Phryganogryllacris nigra sp. nov. is proposed as a new species based on the specimen from Daweishan, Pinbian, Yunnan. New material studied is deposited in Guangxi Normal University, China.